Pengaruh Strategi KWL (Know, Want, Learned) Terhadap Kemampuan Membaca Pemahaman Peserta Didik Di Sekolah Dasar - Feby Inggriyani; Meli Sofi Aptiani (STKIP Andi Matappa Pangkep, 2020)
This study aims to examine the effect of the KWL (Know, Want, Learned) strategy on the reading comprehension ability of fifth grade students of Muslimin Panyawungan 1 and 2. The techniques of research data collection are in the form of tests, observations and interviews. To test the hypothesis that there is an influence or not researchers use a simple linear regression formula. The results showed that the ability to read students 'understanding in the experimental class using the KWL (Know, Want, Learned) strategy was higher than the ability to read students' comprehension in the control class with conventional learning (expository strategy) so that there were differences. This is evidenced from the results of hypothesis testing obtained sig (2-tailed) value of 0.00 <0.05, which means that there are significant differences. Based on the results of the regression test also proves that the KWL (Know, Want, Learned) strategy influences the reading ability of elementary school students' understanding with the results of sig. 0.003 <0.05 so it can be concluded that the use of the KWL (Know, Want, Learned) strategy influences the students' reading comprehension ability in elementary school.